COST STRUCTURE AND INVESTMENT ANALYSIS OF SHEEP ENTERPRISE IN CHITTOOR DISTRICT OF ANDHRA PRADESH - VAMSI, KURAPARTHY; V. PRASAD, R. M.; SURESH, J.; RAVI, A.; EKAMBARAM, B. (Indian Journal of Animal Production and Management, 2017)
ABSTRACTA survey was conducted with a sample of 38 sheep beneficiaries of Rashtriya KrishiVikas Yojana (RKVY) in Chittoor District of Andhra Pradesh. Cost structure and investmentanalysis have been worked out in sheep rearing among the RKVY beneficiaries. The totalcost per unit (20 ewes + 1 ram) was estimated as Rs.1,03,024.32, Rs.73,256.26 andRs.66,909.04 for the first, second and third years, respectively. Net returns per unit wereRs.9157, Rs. 18,222 and Rs.29,056 for the aforesaid years, respectively. The returns perrupee of expenditure tended to increase from 1.09 in the first year to 1.43 in the third year.NPW at 12 per cent rate was Rs.1,43,220 while the Benefit cost ratio was 1.23. Thesenstivity analysis indicated that the enterprise was economically viable even at 24%discount rate.Keywords: Total Costs, Variable costs, Fixed costs, Benefit-Cost ratio.